2018
DOI: 10.1111/rec.12698
|View full text |Cite
|
Sign up to set email alerts
|

A potential method for improving coral self‐attachment

Abstract: Coral restoration is becoming increasingly important to sustain declining reefs. The survival rate of translocated corals in restoration projects is around 65%. This rate is, however, highly variable among projects, with success ranging from 0 to 90% and with detachment being a significant cause of mortality. Improving the speed and strength of coral self-attachment would increase survivorship in translocated corals. To address this need, we tested whether fragments of the scleractinian coral Hydnophora rigida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…[124,125] but see [61]), and yet, in most reports, percent survival of outplants is not clearly reported in accordance to size. The metric that best illustrates the lack of standardised reporting is growth of corals, where a multitude of creative metrics have been used-including linear extension (the summed length of each individual branch within a colony [62,115,126,127], height [128], 'ecological volume' [129,130], branch width [60,131], number of branches [132][133][134], basal width [135] as well as combinations of width, length, height and partial mortality, maximum colony diameter, number of branches, and virtually every other dimension one could think of. The metrics used have such little overlap that comparisons of overall growth among studies are difficult or impossible.…”
Section: Objectives and Monitoringmentioning
confidence: 99%
“…[124,125] but see [61]), and yet, in most reports, percent survival of outplants is not clearly reported in accordance to size. The metric that best illustrates the lack of standardised reporting is growth of corals, where a multitude of creative metrics have been used-including linear extension (the summed length of each individual branch within a colony [62,115,126,127], height [128], 'ecological volume' [129,130], branch width [60,131], number of branches [132][133][134], basal width [135] as well as combinations of width, length, height and partial mortality, maximum colony diameter, number of branches, and virtually every other dimension one could think of. The metrics used have such little overlap that comparisons of overall growth among studies are difficult or impossible.…”
Section: Objectives and Monitoringmentioning
confidence: 99%
“…Numerous approaches for out‐planting asexually propagated coral fragments or sexually propagated larvae on settlement devices have been utilized (Table S1) (Gomez et al ; Boström‐Einarsson et al ). Simple “unattached” methods that connect loose fragments with line can be successful in sheltered reefs (Bowden‐Kerby ; see Forrester et al ), but most approaches need some form of secure attachment in physically dynamic reefs (Tagliafico et al ) since natural self‐attachment rates of corals to the reef are typically low (Smith & Hughes ; Guest et al ). By far the most commonly used approaches are chemical adhesives (glue, epoxy; Dizon et al ; Gomez et al ; cement, Forrester et al ; Kotb ) as well as physical attachment to masonry nails using cable ties (Okubo et al ; Forrester et al ; ; Goergen & Gilliam ) or metal plates/wire (Endo et al ), but also to wooden stakes using fishing line (Dela Cruz et al ).…”
Section: Introductionmentioning
confidence: 99%
“…It is important that the fragment's tissue has grown over the tiles prior to outplanting, as the adhesion of the adhesive often wears off over time. It has been shown that coral fragments from branching species attached upside down grew significantly wider and faster over the tiles than corals attached right side up (Tagliafico et al, 2018), and we recommend this technique to promote rapid tile overgrowth.…”
Section: Screwable Coral Tilesmentioning
confidence: 98%